Chemoinformatics and bioinformatics in the pharmaceutical sciences - Sharma, Navneet (Academic Press, 2021)
"Provides practical information on how to choose and use appropriate computational tools Presents the wide, intersecting fields of chemo-bio-informatics in an easily-accessible format Explores the fundamentals of the emerging field of chemoinformatics and bioinformatics"--